2017
DOI: 10.3390/nano7060129
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Non-Enzymatic Glucose Biosensors Based on Electrochemically Prepared Polypyrrole–Chitosan–Titanium Dioxide Nanocomposite Films

Abstract: The performance of a modified electrode of nanocomposite films consisting of polypyrrole–chitosan–titanium dioxide (Ppy-CS-TiO2) has been explored for the developing a non-enzymatic glucose biosensors. The synergy effect of TiO2 nanoparticles (NPs) and conducting polymer on the current responses of the electrode resulted in greater sensitivity. The incorporation of TiO2 NPs in the nanocomposite films was confirmed by X-ray photoelectron spectroscopy (XPS) spectra. FE-SEM and HR-TEM provided more evidence for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Nonetheless, an Au/CS/TiO 2graphene composite is an interesting alternative to the development of biosensors aimed to the detection of diverse antigens or compounds [104]. Similarly, Al-Mokaram et al [99] fabricate a non-enzymatic glucose biosensor based on electrochemically prepared polypyrrole(Ppy)-CS-TiO 2 nanocomposite film and reported that the device showed good sensitivity over a linear range of 1-14 mM and a detection limit of 614 µM of glucose. The biosensor also exhibited high selectivity and extended useful life with no interference effect in comparison with Ppy-CS without TiO 2 , where TiO 2 increased the electrocatalytic activity of the electrode surface.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, an Au/CS/TiO 2graphene composite is an interesting alternative to the development of biosensors aimed to the detection of diverse antigens or compounds [104]. Similarly, Al-Mokaram et al [99] fabricate a non-enzymatic glucose biosensor based on electrochemically prepared polypyrrole(Ppy)-CS-TiO 2 nanocomposite film and reported that the device showed good sensitivity over a linear range of 1-14 mM and a detection limit of 614 µM of glucose. The biosensor also exhibited high selectivity and extended useful life with no interference effect in comparison with Ppy-CS without TiO 2 , where TiO 2 increased the electrocatalytic activity of the electrode surface.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The biosensor also exhibited high selectivity and extended useful life with no interference effect in comparison with Ppy-CS without TiO 2 , where TiO 2 increased the electrocatalytic activity of the electrode surface. Furthermore, the Ppy-CS-TiO 2 nanocomposite can be used as a glucose sensor due to the ability of composite for glucose oxidation [99]. These results are in line with those of Zhang et al [100], who developed a glucose biosensor on a TiO 2 -multiwall carbon nanotubes-chitosan composite and functionalized with Au nanoparticles, which performed as a good glucose detector with a linear range of 6 µM to 1.2 mM and a detection limit of 0.1 µM.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Schematic representation of the functionalization of polysaccharide-based materials with TiO 2 (a) and their effects on the UV-blocking (b), mechanical (c), gas exchange (d), thermal (e), swelling (f), and adsorptive (g) properties (adapted from Hou et al [34], Goudarzi et al [35], de Moura et al [36], and Dai et al [37]) (figure created in Biorender.com). (a) and their main applications: sensor development (b), antimicrobial activity (c), food and non-food packaging (d), wastewater treatment (e), solar cells and energy storage systems (f), wound-healing (g), and controlled drug release (h) (adapted from de Moura et al [36], Dai et al [37], Ismail et al [38], and Al-Morakam [39]) (table created in Biorender.com).…”
Section: Polysaccharide-tio 2 Hybrid Materialsmentioning
confidence: 99%
“…In contrast to the above enzyme-based biosensors, a nonenzymatic electrochemical device for monitoring glucose was formulated (Al-Mokaram et al 2017). The construct, which was based on a nanocomposite film composed of polypyrrole-chitosantitanium dioxide nanoparticles on ITO glass electrodes, involved redox reactions and exhibited improved glucose oxidation and high electron transfer kinetics.…”
Section: Biosensorsmentioning
confidence: 99%